Pengamatan Karakteristik Parameter Fisika Mutu Air Pada Kolam Terpal Budidaya Ikan Lele (Clarias Sp) Di Desa Iraonogeba, Kecamatan Gunungsitoli - Laia, Maestro (CV. SINAR HOWUHOWU, 2025)
This study focuses on the observation of water properties in the pond. Tarpaulin used for catfish cultivation (Clarias sp). Catfish is one type of fish that lives in freshwater habitats and is often cultivated by the community because of its favorable economic value. In order to support the growth of catfish in the cultivation prosess, the aspect that must get serious attention is water quality, which plays a crucial role in ensuring the success of cultivation.